Pengaruh Penerimaan Teknologi Digital terhadap Kualitas Kinerja Aparatur pada Kantor Kecamatan Mojoroto Kota Kediri - Dicken Naluraning Yasmara; Trenda Aktiva Oktariyanda; Meirinawati Meirinawati; Eva Hany Fanida (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The utilization of digital technology in government administration is a critical measure to improve employee performance and the efficiency of public services. However, the effectiveness of implementing this technology is highly determined by the degree to which employees accept the digital systems being used. This study aims to analyze the impact of digital technology acceptance on employee performance at the Mojoroto District Office in Kediri City. The research employs a quantitative method with an explanatory design. Information was obtained through a questionnaire survey distributed to all employees at the Mojoroto District Office, totaling 30 respondents, using total sampling techniques. Indicators of digital technology adoption were evaluated based on perceptions of benefits, operational ease, social pressure, and infrastructural support, while employee performance was assessed according to the quality of work output and responsibilities. Data analysis involved descriptive statistics, validity and reliability tests, and ordinal linear regression. The study findings indicate that digital technology acceptance has a positive and significant influence on employee performance. The coefficient of determination figure reveals that digital technology adoption can explain a large part of the fluctuations in employee performance, with the remaining variation influenced by variables outside the research model. These results imply that the greater the level of digital technology acceptance, the better the resulting employee performance. This study concludes that strengthening digital capabilities, technical guidance, and institutional support are key strategies for enhancing employee performance and public service quality at the district level.